Adipose Tissue, Adipocyte Differentiation, and Variety of Stem Cells in Tissue Engineering and Regeneration - Babak Pourmollaabbassi; Batool Hashemibeni; Ebrahim Esfandiari (Negah Institute for Scientific Communication, 2016)
Human adipose tissue represents an abundant, practical and appealing source of donor tissue for autologous cell replacement. Recent findings have shown that stem cells within the stromalvascular fraction of adipose tissue display a multilineage developmental potential. Adipose tissue-derived stem cells can be differentiated towards adipogenic, osteogenic, chondrogenic,myogenic and neurogenic lineages. However, the success of using autologous fat tissue grafts to repair soft tissue defects is limited. Researchers are now investigating strategies to engineer volumes of adipose tissue that may be used in these cases. A necessary component for engineering a viable tissue construct is an appropriate cell source. Attempts to engineer adipose tissue have involved using preadipocytes and adipocytes as the base cell source. This research reviews the current state of adipose tissue-engineering methods and describes the shift toward tissue-engineering strategies using stem cells.